Reference Values for Physical Stress Echocardiography in Asymptomatic Patients after Mitral Valve Repair - Jansen, Rosemarijn; Urgel, Kim; Cramer, Maarten J.; van Aarnhem, Egidius E. H. L.; Zwetsloot, Peter P. M.; Doevendans, Pieter A.; Kluin, Jolanda; Chamuleau, Steven A. J. (Frontiers in Surgery, 2018)
Background Clinical decision-making in symptomatic patients after mitral valve (MV) repair remains challenging as echocardiographic reference values are lacking. In native MV disease intervention is recommended for mean transmitral pressure gradient (TPG) >15 mmHg or systolic pulmonary artery pressure (SPAP) >60 mmHg at peak exercise. Insight into standard stress echo parameters after MV repair may therefore aid to clinical decision-making during follow-up. Hypothesis Stress echocardiography derived parameters in asymptomatic patients after successful MV repair differ from current guidelines for native valves. Material and methods In 25 patients (NYHA I) after MV repair stress echocardiography was performed on a semi-supine bicycle. Doppler flow records and MV related hemodynamics at rest and peak were obtained. Linear regression analysis was performed for mean TPG and SPAP at peak, using predetermined variables and confounders. Results Mean TPG at rest (3.2 ± 1.4 mmHg) significantly increased at peak (15.0 ± 3.4 mmHg) but was always <25 mmHg. Mean SPAP at rest (21.4 ± 3.8 mmHg) significantly increased at peak (41.8 ± 8.9 mmHg) but was never >57 mmHg. Only the indexed MV ring diameter was inversely correlated to mean TPG at peak in a multivariable model. Conclusion In contrast to current recommendations in native MV disease, our data indicate that the standard value for mean TPG during stress echocardiography in asymptomatic patients after successful MV repair was above the guideline threshold of 15 mmHg in >50%, but always <25 mmHg. For SPAP, patients never reached the guideline cutoff (60 mmHg). Long-term follow-up data are needed to provide insight in clinical consequences. Baseline stress echocardiography may indicate individual reference values to compare with during follow-up. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT02371863?term=chamuleau+AND+Mitral&rank=1.